The Situation of Innovative Entrepreneurship Courses Offered by Technological Colleges and Universities in Taiwan - Chang, Jen-Chia; Chen, Xing-Yu (Advances in Social Sciences Research Journal, 2023)
Babson College has become a model for the advancement of entrepreneurship education in the United States. Its personalized entrepreneurship education programs foster entrepreneurial elites, making it a model for Taiwan’s entrepreneurship education development. Its personalized entrepreneurship education programs foster entrepreneurial elites, making it a model for Taiwan’s entrepreneurship education development.Additionally, Taiwan has incorporated and adapted a series of entrepreneurship education courses. In recent years, the government has promoted practical projects and simulation entrepreneurial competitions aggressively. The entrepreneurial theories and practical experiences are combined to provide more comprehensive and structured learning courses for entrepreneurial students. In the contemporary social environment, innovation and entrepreneurship have become vital economic engines. Consequently, it is crucial to cultivate entrepreneurialism and entrepreneurial skills in students. Students and faculty in Taiwan’s higher education system have access to a plethora of excellent learning platforms where they can acquire a vast array of practical knowledge and skills. In entrepreneurship education, schools therefore adopt Babson College’s methodology and planning. In Taiwanese courses, the current situation is reviewed and related feedback opinions are collected in order to strengthen the prior knowledge of students and increase their employment competitiveness, thereby serving as the link between the self-awareness of students and their understanding of themselves.